Response Of Geraniol Derivative And Cymbopogon Citratus Leaves Extract Against Periimplantitits Causing Pathogens (Journal of Pharmaceutical Negative Results, 2022)
Periimplantitis due to pathogenic bacteria is the chief cause for the dental implants failure. Evidences over S. aureus and E. coli to trigger periimplantitis, antimicrobial potential of Cymbopogon citratus and geraniol intended present study to compare the antimicrobial potential of hydrazide derivative of geraniol (HDG) and Cymbopogon citratus leaves extract (CCLE) against periimplantitis causing pathogens (PCP). Present study involved synthesis of HDG and preparation of CCLE. The HDG was characterized using ATR-IR, 1H-NMR and Mass spectrometric data. Both HDG and CCLE were tested for antimicrobial potential against periimplantitis causing pathogens (PCP), namely: Escherichia coli and Staphylococcus aureus. Among both, the HDG exhibited much higher antimicrobial potential when compared with CCLE. Based on the resultant data present study concludes that HDG possess high inhibition potential against PCP and recommends that HDG should be further evaluated to support its clinical importance.